Prefronto‐temporal white matter microstructural alterations 20 years after the diagnosis of type 1 diabetes mellitus. Issue 3 (20th September 2017) - Yoon, Sujung; Kim, Jungyoon; Musen, Gail; Renshaw, Perry F; Hwang, Jaeuk; Bolo, Nicolas R; Kim, Jieun E; Simonson, Donald C; Weinger, Katie; Ryan, Christopher M; Lyoo, In Kyoon; Jacobson, Alan M
Abstract : Objective: Microvascular pathophysiology that uniquely manifests as white matter (WM) abnormalities is often implicated in type 1 diabetes mellitus (T1DM)‐related central nervous system (CNS) complications. This study sought to identify regional WM abnormalities in young adults diagnosed with T1DM and further examine their association with cognitive and emotional dysfunction. Research Design and Methods: Diffusion tensor images (DTI) obtained from 34 young adults with T1DM for ≥15 years (mean duration, 20.9 years), and 16 age‐ and sex‐matched healthy control subjects were analyzed using tract‐based spatial statistics. Fractional anisotropy (FA) values of the whole brain were analyzed, and their associations with memory function and depressive symptoms were assessed. Results: Whole brain voxel‐wise analyses showed that T1DM‐related FA reductions were most prominent within the fronto‐temporo‐parietal regions of the brain. Reduced FA values in the bilateral superior longitudinal fasciculi, at which group differences were most prominent, correlated with lower working memory performance in young adults with T1DM (left, P < .001; right, P = .009). Subsyndromal depressive symptoms were also associated with lower FA values in the right inferior fronto‐occipital fasciculus ( P = .004). Conclusion: Widespread WM microstructural abnormalities in the fronto‐temporo‐parietal brain regions, which are associated with emotional and cognitive dysfunction, may be a contributing factor to the neural mechanisms underlying T1DM‐related CNS complications, thus affecting the quality of life in young adults with T1DM.